2017
DOI: 10.1380/ejssnt.2017.96
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of Silicon-Embedded Ni(110)

Abstract: First-principles total energy calculations were performed to investigate stable atomic structures for the displacive adsorption of silicon on the Ni(110) surface. Gibbs free energies were compared for 0-4 silicon atoms embedded into the top layer in a 2×2 unit for the Ni(110) surface. When a half monolayer of Si was embedded, the p(1×2) structure had the lowest energy, and the c(2×2) structure had only 13 meV/1×1 higher energy than the p(1×2) structure. By extending to a 4×2 unit, the c(4×2) structures had alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…The exchange energy was estimated to be 0.79 eV from the difference of band edge energies between the majority spins (−0.49 eV) and the minority spins (+0.30 eV). The exchange energy is in good agreement with our previous calculations for the Ni(110) surface [10]. Top Ni on the Ni(100) surface in Figure 5(b) shows similar PDOS, but the 3d band is slightly narrower than the bulk band, which is also similar to our previous calculation for the Ni(110) surface [10].…”
Section: B Atomic Configuration and Band Structure For The Low Energy Configurationsupporting
confidence: 91%
See 3 more Smart Citations
“…The exchange energy was estimated to be 0.79 eV from the difference of band edge energies between the majority spins (−0.49 eV) and the minority spins (+0.30 eV). The exchange energy is in good agreement with our previous calculations for the Ni(110) surface [10]. Top Ni on the Ni(100) surface in Figure 5(b) shows similar PDOS, but the 3d band is slightly narrower than the bulk band, which is also similar to our previous calculation for the Ni(110) surface [10].…”
Section: B Atomic Configuration and Band Structure For The Low Energy Configurationsupporting
confidence: 91%
“…The exchange energy is in good agreement with our previous calculations for the Ni(110) surface [10]. Top Ni on the Ni(100) surface in Figure 5(b) shows similar PDOS, but the 3d band is slightly narrower than the bulk band, which is also similar to our previous calculation for the Ni(110) surface [10]. On the other hand, the exchange splitting of surface Ni was 0.83 eV (−0.46 eV for majority spins and +0.37 eV for minority spins), which is larger than that of bulk, and gives a larger magnetic moment of 0.73 μB compared to the bulk value of 0.64 μ B .…”
Section: B Atomic Configuration and Band Structure For The Low Energy Configurationsupporting
confidence: 91%
See 2 more Smart Citations
“…Indeed, only a few reports discussing the structure and reaction of silicidation on metal surfaces have been published. [25][26][27][28][29][30][31] It was reported that 2 × 2 and 3 3 -R30°structures are formed by exposing a Ni(111) surface to silane at high temperatures. 25) In a later study, it was found that a one-third monolayer of Si is involved in the 3 3 -R30°structure, indicating the formation of 2-D Ni 2 Si.…”
Section: Introductionmentioning
confidence: 99%